PENGENALAN OBJEK CITRA SAMPAH ANORGANIK DI LINGKUNGAN UPN VETERAN JAKARTA MENGGUNAKANMETODE YOU ONLY LOOK ONCE VERSI 3 - Muthiara Panghurina (2023)
Garbage is everything left over from daily human activities that has been used and is in solid form that is no longer needed so it is thrown away. Due to the large number of types of waste generated, sometimes it creates problems such as how to manage the large amount of waste so that it can be reduced. In the UPN Veteran Jakarta environment, waste management mobilizes cleaning staff to transport and clean the surrounding environment. The process of managing waste in the UPN Veteran Jakarta environment is not carried out by segregation in its management because waste is directly collected into one organic and inorganic one and thrown away. In this study, researchers took the initiative to detect garbage objects in the UPN Veteran Jakarta environment. The method used is object detection with YOLOv3. Based on the experiments that have been carried out three times, the best results were obtained in experiment 3 which used 80% train data, 10% validation and 10% test with an average of 0.933. Where the average value is obtained from the precision 0.979, recall 0.882 and mAP 0.94.